O outsider em Caio Fernando Abreu - Baruffi, Afani Carla (2018)
Our study analyzes the representation of the outsider having as corpus the tale “O afogado” present in the work O ovo apunhalado (1975) by Caio Fernando Abreu. In this short story we will try to show how deep and current this solitary subject is that acts transgressively to break with the world around him, locating in the text the proximity and distance with the classic outsider studied by authors like Colin Wilson (1985). The research, which approaches some relationsc dhips of the outsider with the contemporary literature, will seek to identify how this subject in disarray with the environment seeks, through small acts of rupture in the spaces that the social group leaves evident, access to their impasses and inquiries. The work, of a qualitative and bibliographical nature, also proposes a positive look under the mismatch.